Analysis of responses of the health care workers recovered from COVID‐19 on convalescent plasma donation by apheresis: A single‐center survey study. Issue 3 (4th February 2022) - Sahu, Ansuman; Prakash, Satya; Singh, Arvind Kumar; Mukherjee, Somnath
Abstract: Background: The COVID‐19 convalescent plasma (CCP) has been tried as a therapy in moderate COVID‐19 pneumonia. Donation of CCP requires motivation from recovered patients. This study evaluated the response of such recovered health care workers (HCWs) when they were motivated for CCP donation. Methods: An interview‐based survey was carried out with recovered HCWs as study participants between August 2020 and November 2020. A qualified social worker explained the details of CCP donation over a mobile call; he clarified all their doubts and motivated them for the plasma donation. Their responses were recorded as "interested" or "not interested" followed by analysis. Results: We tried to call 624 recovered HCWs, but could not reach 213, and the final group available for the study was 411 participants. Of these 411, 186 were deferred. Finally, we analyzed a total of 225 responses. Eventually, 105 out of 225 HCWs (47%) were interested; there were no significant differences in responses among males and females and between different age groups (<.001) and the "doctors" designation category ( P = .01) had a maximum number of "interested" responses. In multivariate logistic regression, only the "interested" responses of the doctors were significantly higher after adjusting the confounding effect of the "graduate and above" educational qualification category. Conclusion: This study found that nearly half of the eligible HCWs were interested in CCP donation. The educational qualification and designation among the recovered HCWs had an impact on CCP donation interest. The doctors were more interested in CCP donation compared to others.